Internet Use Adoption Among Academicians : Comparing Innovative Adopters and Other Adopter Types. - Norazah Mohd Suki; Norbayah Mohd Suki (2006)
Online shopping represents an innovation to be adopted or rejected by online consumersglobally. Previous experiences and knowledge of innovation are the main factors affectingpeopleâs willingness to adopt a new innovation. We explore how Internet use differsbetween academicians who are innovative adopters and other types of adopters.Academicians who are innovative adopters are hypothesized to: have more years of experience on online shopping, have greater frequency of purchase, and pay a higher price for items purchased online.Data were collected from 301 respondents. Results provide new perspective on innovativeadopters among Malaysian academicians; they have less experience than other adopters inshopping for products online, make fewer purchases online and pay small amount ofmoney in shopping for products online than other adopters. Directions for future research are also discussed.